“Boys don’t cry do they?” A reflexive thematic analysis of education professionals’ perspectives regarding secondary school males identified as SEMH who have been permanently excluded. - Hateley, Emma Louise (2024)
A young person who is identified as having SEMH (social, emotional and mental health) needs as per the Special Educational Needs (SEND) Code of Practice (2015) is 3.8 times more likely to be permanently excluded than pupils with no identified SEND need (Timpson, 2019). The Department of Education (2023) permanent exclusion data identifies males as more likely to be permanently excluded year on year, particularly within their secondary education, indicating a need to explore the link between SEMH, males and permanent exclusion, particularly as research suggests that males may not seek support due to socially constructed gender norms of masculinity. The aims of this research were to explore the perceptions of educational professionals with regard to the barriers and protective factors concerning the inclusion of males identified as having SEMH needs, who have been permanently excluded and reintegrated into mainstream secondary settings. Five participants from a range of professions within the SEMH, permanent exclusion and reintegration context were interviewed using semi-structured interviews. Two overarching themes were created: ‘Power inequality and rejection supports permanent exclusion and prevents successful reintegration’ and ‘The system needs support.’ Five main themes were also produced including, power and policies perpetuate conformity, rejection undermines belonging, bravado: Boys don’t talk they fight, the importance of multi-agency collaboration and adult upskilling. Each theme is discussed in relation to exploring the perceived barriers and supportive factors related to the inclusion, permanent exclusion and reintegration of males who are identified as SEMH, with consideration to the next steps and the implications for the Government, schools and educational psychology services. The positionality of the researcher is described including epistemological assumptions, with reflection regarding the study's limitations and strengths, as well as suggestions for future research.